Mechanical ventilation and weaning - Mancebo, J; Vincent, Jean Louis (Springer, 2003)
Hospital de la Sante Creu i Sant Pau, Barcelona, Spain. Text provides information on the management of patients utilizing mechanical ventilation. Covers what to do if the patient resists the ventilator, non-invasive ventilation, and weaning-induced cardiac failure. Softcover, hardcover listed in approval week 2001-49.
Update in intesive care medicine
Keywords: odpojení od ventilátoru; etika, bioetika, lékařská etika; Ventilator Weaning